Tracking down the rare ciliate biosphere - Weiss, James; Esteban, Genoveva F. (Frontiers in Protistology, 2024)
In this study, we aim to demonstrate the richness of the rare ciliate biosphere and hypothesize on the reasons of rarity by combining morphological and ecological details on some exceedingly rare ciliates. The study includes the first report of different morphotypes of Dactylochlamys since 1928, first report of Penardiella undulata since 1930, second report of Penardiella interrupta since 1930, and an undescribed Penardiella species. The first report of Bryophyllum caudatum since 1933, microscopical observations and taxonomical discussion of the rare Legendrea bellerophon and of and undescribed Legendrea species. A new Apertospathula sp. with prokaryotic endosymbionts is described. The rarity of these species is explored and explained by their anaerobic metabolism combined with their prey selection.